PENGAWASAN ADMINISTRATIF TATA USAHA KAYU DI TPK DAN LOGPOND HPH DENGAN PROGRAM KOMPUTER - Hariyatno Dwiprabowo (Jurnal Penelitian Hasil Hutan, 1992)
Ministry of forestry requires the forest  concession holders  to fill in   logs  administrative forms  containing  log records  to supervise Iogs  production and circulation  in forest  concessions. However, large .amount  of logs produced  has prevented  the provincial  forest  service and forest  district from conducting through examination on the documents turned in by concessionaries.In this study, a computer program intended to help accomplishing the task is created and tried out documents that must be filled  in at logyard and logpond of concession. Using simulated  logs data the program run on PC could find  some deviation in the documents presented in terms of logs statistics.